Biofilter based on a biofilm immobilized on geo-textile sheets for rapid atrazine biodegradation. (November 2015) - Swissa, Nissim; Nitzan, Yeshayahu; Anker, Yaakov; Cahan, Rivka
Abstract: In this research, three carriers: coal bottom ash, glass fibers cloth and geo-textile sheets made of polyethylene terephthalate (PET) fibers were compared as substrata for biofilm attachment of atrazine-biodegrading bacterial cells. The calculated CFU for a 1 g carrier of coal bottom ash, glass fibers cloth and PET geo-sheet was 9.4 × 10 6, 9.6 × 10 7 and 1.1 × 10 8, respectively. Atrazine degradation by the biofilm attached to glass fibers cloth and PET geo-textile sheet reached 100% within 6 h, while biodegradation by the biofilm attached to coal bottom ash reached only 69 ± 4% within 8 h. Two biofilters were designed and constructed: a sparsely packed biofilter in which the PET geo-textile sheets were placed at a distance of 2 cm from each other and a densely packed biofilter in which the PET geo-textile sheets were placed adjacent to each other (with no distance between them). About 100% of atrazine biodegradation (initial concentration of 75 mg L −1 ) occurred within 4 and 5 h in the densely packed and in the sparsely packed biofilms, respectively. The biofilter facility was examined for atrazine degradation in the presence of sludge and was found to degrade atrazine (initial concentration of 30 mg L −1 ) within 4 h. Several methods were used to prepare biofilms immobilized on PET geo-textile sheets for prolonging storage. It was found that freezing at −20 °C with glycerol and storage at −20 °C led to an atrazine biodegradation rate that was similar to a biofilter with a fresh biofilm. To the best of our knowledge, this is the first study to describe atrazine degradation in a biofilter facility based on a biofilm immobilized on PET geo-textile sheets. Highlights: Biofilm was grown on coal bottom ash, glass fibers and PET geo-textile sheets. A biofilter based on PET geo-textile sheets showed atrazine degradation within 4 h. Methods for prolonged storage of PET geo-textile sheets with immobilized bacteria.